1996
DOI: 10.1021/la950746o
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy Studies on Sterically-Stabilized Polypyrrole Particles

Abstract: The surface composition of a sterically-stabilized polypyrrole colloid has been examined by X-ray photoelectron spectroscopy (XPS). The sulfur atom of the polyelectrolyte stabilizer poly(potassium 3-sulfopropyl methacrylate) [PKSPM] and the nitrogen atom of the polypyrrole were used as unique elemental markers for each component. The S/N atomic ratio at the particle surface determined using XPS was found to be significantly higher than the corresponding ‘macroscopic' S/N atomic ratio calculated from elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…8 The sulfonate group is known to be an efficient dopant anion for PPy and has stronger interactions with PPy compared with chloride ions. 8,27,28 It has been confirmed that the PPy-Pd nanocomposite particles were doped with sulfonate groups rather than chloride ions by X-ray photoelectron spectroscopy studies. 8 Therefore, it can be expected that the PLSSA colloidal stabilizer is adsorbed onto the surfaces of the PPy-Pd nanocomposite particles as a polymeric dopant anion ( Figure 1).…”
Section: Resultsmentioning
confidence: 82%
“…8 The sulfonate group is known to be an efficient dopant anion for PPy and has stronger interactions with PPy compared with chloride ions. 8,27,28 It has been confirmed that the PPy-Pd nanocomposite particles were doped with sulfonate groups rather than chloride ions by X-ray photoelectron spectroscopy studies. 8 Therefore, it can be expected that the PLSSA colloidal stabilizer is adsorbed onto the surfaces of the PPy-Pd nanocomposite particles as a polymeric dopant anion ( Figure 1).…”
Section: Resultsmentioning
confidence: 82%
“…8a) shows the same peaks as the sample prepared in absence of PVAL. Nevertheless the addition of PVAL to the reaction media resulted in the adsorption of this oxygen containing polymer on the surface of the colloids, as evidenced by the reduction of the S 2p signal intensity and the increase of the O/C and O/N ratio, similar to chemically synthesized PPy colloids stabilized with polyelectrolytes [38]. In fact, the deconvolution of the C 1s peak from the colloids (Fig.…”
Section: Polypyrrole Thin Films and Colloidsmentioning
confidence: 73%
“…3). Typically, the polymeric stabiliser is merely physically adsorbed onto the surface of the polypyrrole particles via either hydrogen bonding 21 or electrostatics; 22 although chemicallygrafted stabilisers have also been developed, 23,24 this latter approach has not yet been utilised for space science applications. The biocompatible nature of polypyrrole, coupled with its intense intrinsic pigmentation and strong absorption of near-IR radiation, has led to various biomedical applications being explored for such polypyrrole-based nanoparticles.…”
Section: Sterically-stabilised Polypyrrole Latexesmentioning
confidence: 99%